STARTING POINTS FOR CHANGING THE WAY HOW BASIC MANAGEMENET COURSE IS TOUGHT AT THE UNIVERSITY - KONVALINKA, Michal; PROCHÁZKA, Anthony David (Trends in education, 2017)
This article concerns a specific experience with realising student feedback at the university. The research is embedded in a narrow context and identifies interesting aspects of student's attitudes. The research was conducted through a questionnaire survey for three consecutive periods (semesters) and focuses on several areas. The authors explore the students' motivation to study and their incentives to attain good grades. It also discovers the manner and duration of the students' preparation for their final test and last, but not least, it evaluates the difficulty of the subject. The questionnaire also contains several open-ended questions that reveal surprising insights. The conclusions are considered with the fact in mind that students did not achieve excellent grades in their final evaluations. The research is particularly beneficial, not only for educators and fellow researchers, but also for developers of study programs and guarantors of subjects at universities.
Keywords: education; higher education; feedback; student motivation